Loss of BAP1 Expression Occurs Frequently in Intrahepatic Cholangiocarcinoma. Issue 2 (January 2016) - Andrici, Juliana; Goeppert, Benjamin; Sioson, Loretta; Clarkson, Adele; Renner, Marcus; Stenzinger, Albrecht; Tayao, Michael; Watson, Nicole; Farzin, Mahtab; Toon, Christopher W.; Smith, Ross C.; Mittal, Anubhav; et al.
Abstract : Abstract: BRCA1-associated protein 1 (BAP1) is a deubiquitinating enzyme that functions as a tumor suppressor gene. Double hit BAP1 inactivation has been reported in a range of tumor types, including intrahepatic cholangiocarcinoma (ICC), sometimes in association with germline mutation. We performed immunohistochemistry for BAP1 on a well-characterized cohort of 211 ICC patients undergoing surgical resection with curative intent at 3 institutions based in 3 different countries. The median age at diagnosis was 65 years (range, 36.5–86) and 108 (51%) were men. Negative staining for BAP1 (defined as completely absent nuclear staining in the presence of positive internal controls in nonneoplastic cells) occurred in 55 ICCs (26%). BAP1 loss predicted a strong trend toward improved median survival of 40.80 months (95% CI, 28.14–53.46) versus 24.87 months (95% CI, 18.73–31.01), P = 0.059). In a multivariate model including age, sex, BAP1 status, tumor stage, tumor grade, lymphovascular invasion, and tumor size, female sex was associated with improved survival (hazard ratio [HR] 0.54; 95% CI, 0.34–0.85), while advanced tumor stage and lymphovascular invasion (HR 1.89; 95% CI, 1.09–3.28) correlated with decreased survival. In a multivariate analysis, high grade tumors were associated with BAP1 loss (odds ratio [OR] 3.32; 95% CI, 1.29–8.55), while lymphatic invasion was inversely associated with BAP1 loss (OR 0.36; 95% CI, 0.13–0.99). In conclusion, we observed a trend toward improved prognosis in ICC associated with absent expression of BAP1 and an association of BAP1 loss with higher histological grade and absent lymphatic invasion. Female sex was associated with improved survival while advanced tumor stage and lymphatic invasion were associated with decreased survival.